Implementation Of Plant Cultivation Through Social Forestry In An Effort To Reduce The Climate Crisis In Dusun Jepang Of Bojonegoro - Arianti, Marshiela Putri; Alawi*, Muammar (Universitas Syiah Kuala, 2024)
This research was conducted in the Dusun Jepang of Margomulyo Village, Bojonegoro Regency through village development activities from the National Development University